Quality of Experience Metric of Streaming Video: A survey - Ghani, Rana Fareed; Ajrash, Amal Sufiuh (Iraqi Journal of Science, 2018)
Technological development in the last years leads to increase the access speed in the internet networks that allow a huge number of users watching videos online. Video streaming important type in the real-time video sessions and one of the most popular applications in networking systems. The Quality of Service (QoS) techniques give us indicate to the effect of multimedia traffic on the network performance, but this techniques do not reflect the user perception. Using QoS and Quality of Experience (QoE) together can give guarantee to the distribution of video content according to video content characteristics and the user experience . To measure the users’ perception of the quality we use Quality of Experience (QoE) metric . Here , in complete we display what the QoE and QoS mean and what the difference between them, list the techniques used to measured them ; then we display a study of the literature on different tools and measurement methodologies that have been proposed to measure or predict the QoE of video streaming services.